2011
DOI: 10.1007/s11661-011-0679-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Stress-Induced Formation of R-Phase in Ultra-Fine-Grained Ni-Rich NiTi Shape Memory Alloys

Abstract: Phase transformations in binary ultra-fine-grained (UFG) pseudoelastic NiTi wires were studied in a wide temperature range using mechanical loading/unloading experiments, resistance measurements, differential scanning calorimetry (DSC), thermal infrared imaging, and transmission electron microscopy (TEM). The formation of R-phase can be detected in the mechanical experiments. It is shown that the stress-strain response of the R-phase can be isolated from the overall stress-strain data. The R-phase always forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…Recently, it was shown that the width of the mechanical hysteresis in PE SMAs is governed by the crystallographic compatibility between martensite and austenite [21]. It is important to highlight that the mechanical properties of PE NiTi show a very strong Clausius-Clapeyron type of temperature dependence [22]. An increase in temperature by 10 K, for example, is associated with an increase in both plateau stresses by about 65 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that the width of the mechanical hysteresis in PE SMAs is governed by the crystallographic compatibility between martensite and austenite [21]. It is important to highlight that the mechanical properties of PE NiTi show a very strong Clausius-Clapeyron type of temperature dependence [22]. An increase in temperature by 10 K, for example, is associated with an increase in both plateau stresses by about 65 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…1a. Olbricht et al [22] showed that higher plateau stresses (caused by higher temperatures) can promote irreversible deformation based on dislocation plasticity. Therefore, PE can only be applied within a certain temperature window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitinol can exhibit secondary deformation during mechanical testing, such as stress-induced martensite, and this has contributed to problems in being able to measure its mechanical properties [22]. Therefore, using conventional mechanical testing methods to measure the material properties of Nitinol, such as elastic modulus, have often not been successful [24].…”
Section: B Nitinol For Tuneable Resonance Devicesmentioning
confidence: 99%
“…Like the A $ M transformation, the A $ R transformation also shows shape memory effect and pseudoelasticity [8,9]. Moreover, the A $ R transformation shows attractive properties, such as narrow thermal or stress hysteresis [10,11], fast response to temperature change [1,12,13], as well as high functional stability during thermomechanical cycling [13][14][15][16]. Based on these unique properties, although the transformation strain is small (*1 %) [9,17], various devices have been developed applying the A $ R transformation after proper structural design [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%